The elements : a novel [large type] - Boyne, John, 1971- (Thorndike Press large print top shelf., 2025)
"In The elements, acclaimed Irish novelis.t John Boyne has created an epic saga that weaves together four interconnected narratives, each representing a different perspective on crime: the enabler, the accomplice, the perpetrator, and the victim. The narrative follows a mother on the run from her past, a young soccer star facing a trial, a successful surgeon grappling with childhood trauma, and a father on a transformative journey with his son. Each is somehow connected to the next, and as the story unfolds, their lives intersect in unimaginable ways"--